(3QSGdI aj Yde GdaQGFVs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; bjd GdaQGFV LeY aQjVI hjbGd aQV GdQLGds
(3BNQgG (B:s
(3HfJ hCNJ dCH ddHfJ GdfUa hGdHGbj ddCNJ ddCH HfJ hCNJ dCHhjf hCN hCNJ ddCH ddHfJ GdfUa hddCNJ dCHhjf GdfUa hdG TjA ddCNJ hGdCN dCHs
(3JHUQI GdYfhGf (B:s
(3QSGdI aj Yde GdaQGFV ebJHSI ef cJGH GdegPHs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdaQGFVs